Rancangan Sistem Informasi Berbasis Web Mobile Potensi Lampung Tengah - Fandi Achmad; Fiqih Satria (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2018)
Technology is growing in the current era of development encourages each region to take advantage of technology in supporting the progress of the area. One of the aspects that become the foundation in advancing the region is the potential of the region. Understanding the potential of the region as a whole will facilitate the government in building facilities and infrastructure. Central Lampung regency is one of the districts contained in Lampung Province which has considerable regional potential. But many people who do not know the potential of the area is caused by lack of information. Through the potential information system of Central Lampung District based Website, the public is expected to know information about the potential of Central Lampung Regency. Making of this potential information system of area is built by collecting data based on system planning, that is context diagram, DFD (Data Flow Diagram), and ERD (Entity Relationship Diagram). With making of potency information system area, people will easy to get information through fast access and efficient.